Global governance and Japan the institutional architecture - Hook, Glenn D; Dobson, Hugo (Routledge, 2007)
Examines the institutional mechanisms of governance at the global level and provides evidence of the role Japan plays in these institutions. Serving as an introduction to the concept of global governance, this volume analyzes how global governance actually works through the global institutional mechanisms of governance.